The subak lexicon based on local wisdom as the development of educational tourism promotion in the Subak Teba Majalangu, Kesiman Kertalangu Village, Bali - Ekasani, Kadek Ayu; Lestari, Denok; Sudarsana, Cokorda Istri Sri Apriyani; Mirayanti, Ni Luh Diah (Politeknik Negeri Bali, 2022)
The Subak Teba Majalangu Kesiman Kertalangu Village is intended for the community and introduces nature-based education. The concept of educational tourism itself is focused on nature tourism, namely agriculture where the activities will be more emphasized how to plow, hoe, make seeds, plant rice, fertilize, harvest, and other agricultural activities. The purpose of this study was to create a mapping of the lexicon containing local wisdom in the Subak Teba Majalangu. This research has an urgency to support the preservation of regional culture, as well as preserve regional languages as the cultural wealth of the archipelago. The qualitative method with an anthropological approach was used in this research. The data will be collected through interviews with selected informants, do observation, then make an analysis based on domains, and present using tables and images. The result of this research is there are five groups of Subak, which are the group of tillage tools, weed controller, various kinds of sickles, treating and monitoring tools, and harvest tools. Those tools have their functions and purposes to help farmers starting from tilling the land, planting, and tending until harvesting. Although some of the tools are no longer used by the farmer, this research can be used to preserve the Balinese culture especially the lexicon of Subak, the Balinese traditional irrigation system